2017
DOI: 10.5230/jgc.2017.17.e39
|View full text |Cite
|
Sign up to set email alerts
|

Using Quality of Life Scales with Nutritional Relevance after Gastrectomy: a Challenge for Providing Personalized Treatment

Abstract: PurposeThis study evaluated the changes in nutritional status based on quality of life (QoL) item-level analysis to determine whether individual QoL responses might facilitate personal clinical impact.Materials and MethodsThis study retrospectively evaluated QoL data obtained by the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-Core 30 (QLQ-C30) and Quality of Life Questionnaire-Stomach (QLQ-STO22) as well as metabolic-nutritional data obtained by bioelectrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Previous studies have reported total weight loss of 10e15% in the early postoperative phase [29,30]. In the long term permanent weight loss of 8.3e13.6% has been reported [7,31,32]. We observed that 45% of the patients had a persistent weight loss of >10% at follow up, which is consistent with previous findings, where 67% of subjects had >10% weight loss at two years postoperatively [12].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported total weight loss of 10e15% in the early postoperative phase [29,30]. In the long term permanent weight loss of 8.3e13.6% has been reported [7,31,32]. We observed that 45% of the patients had a persistent weight loss of >10% at follow up, which is consistent with previous findings, where 67% of subjects had >10% weight loss at two years postoperatively [12].…”
Section: Discussionsupporting
confidence: 92%
“…This condition presents with symptoms such as an abdominal burning sensation, belching, acid reflux, and nausea and vomiting, which seriously affect postoperative diet and quality of life, thereby adversely affecting the physical and mental health of these patients. Some even suffer from depression, anxiety and malnutrition [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions, together with the rare congenital pathology known as microgastria [ 2 ], could cause a high morbidity due to reduced gastric volume and related loss of digestive and reservoir function. Following total or partial gastrectomy, dumping syndrome and reduced intestinal adsorption of vitamins are indeed to be kept in mind dealing with children since they can influence life-long quality-of-life [ 3 ].…”
Section: Introductionmentioning
confidence: 99%